Transformasi Iklan Radio Dalam Menselaraskan Promosi dan Layanan Masyarakat - Aula, Miftachul; Sutamaji (Communicator: Journal of Communication, 2024)
Important elements are very much needed in completing the creation of advertisements in order to tidy up and make audio more useful and pleasant to listen to. This study aims to find out how to formulate an advertisement editing strategy, how to implement an advertisement editing strategy, and how to evaluate an advertisement editing strategy in developing public services at Radio RSAL FM. This study uses a qualitative methodology derived from an interpretative or subjective approach. This interpretive approach has two variants, namely critical and constructivism. This study departs from a critical approach as with framing analysis in general. With a qualitative methodology that emphasizes more on the issue of depth (quality) of data rather than on the amount (quantity) of data. Based on data in the field, researchers found the fact that Radio RSAL. FM Nganjuk, from the preparation, planning, implementation, and supervision of the delivery of advertisements, has been very effective. Advertising is a form of message delivery like other communication activities. Advertising is a communication process that has important power as a marketing tool in helping to sell goods, provide services, and ideas through certain channels or ideas in a persuasive form.